Doping-dependent electronic structure of cuprates studied using angle-scanned photoemission - Schwaller, P.; Greber, T.; Aebi, Philipp; Singer, J. M.; Berger, H.; Forró, L.; Osterwalder, J. (My University, 2000)
Full k

-maps of the electronic structure near the Fermi level of differently doped cuprates measured with angle-scanned photoelectron spectroscopy are presented. The valence band maximum of the antiferromagnetic insulator Sr2CuO2Cl2, which is taken as a representative of an undoped cuprate, and the Fermi surfaces of overdoped, optimally doped and underdoped Bi2Sr2CaCu2O8+' high-temperature superconductors are mapped in the normal state. The results confirm the existence of large Luttinger Fermi surfaces at high doping with a Fermi surface volume proportional to (1+x), where x is the hole concentration. At very low doping, however, we find that this assumption based on Luttinger's theorem is not fulfilled. This implies a change in the topology of the Fermi surface. Furthermore the intensity of the shadow bands observed on the Fermi surface of Bi2Sr2CaCu2O8+' as a function of the doping is discussed.